2018
DOI: 10.1002/cpt.979
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Targeting of Red Blood Cells to Improve Tissue Oxygenation

Abstract: Disruption of microvascular blood flow is a common cause of tissue hypoxia in disease, yet no therapies are available that directly target the microvasculature to improve tissue oxygenation. Red blood cells (RBCs) autoregulate blood flow through S‐nitroso‐hemoglobin (SNO‐Hb)‐mediated export of nitric oxide (NO) bioactivity. We therefore tested the idea that pharmacological enhancement of RBCs using the S‐nitrosylating agent ethyl nitrite (ENO) may provide a novel approach to improve tissue oxygenation. Serial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Indeed, several clinical 24,25 and preclinical trials 26,27 have demonstrated the therapeutic benefits of renitrosylation, which acts to restore or enhance RBC-derived NO bioactivity. Of specific relevance to the current findings, we recently demonstrated in a clinical trial that pharmacological elevation of SNO-Hb increased StO 2 in healthy subjects under hypoxia (FiO 2 =0.12) 28 . And in a large animal preclinical model of donor support, increasing SNO-Hb after BD improved tissue blood flow and oxygenation, reduced markers of immune activation and cellular injury, and preserved organ function 29 .…”
Section: Discussionsupporting
confidence: 58%
“…Indeed, several clinical 24,25 and preclinical trials 26,27 have demonstrated the therapeutic benefits of renitrosylation, which acts to restore or enhance RBC-derived NO bioactivity. Of specific relevance to the current findings, we recently demonstrated in a clinical trial that pharmacological elevation of SNO-Hb increased StO 2 in healthy subjects under hypoxia (FiO 2 =0.12) 28 . And in a large animal preclinical model of donor support, increasing SNO-Hb after BD improved tissue blood flow and oxygenation, reduced markers of immune activation and cellular injury, and preserved organ function 29 .…”
Section: Discussionsupporting
confidence: 58%
“…Yet another potentially interesting nitrosation reaction occurs between ethanol and nitrite in the acidic stomach to form the highly potent vasodilator ethyl nitrite (Gago et al, 2008), an organic nitrite that has been used as a pulmonary vasodilator in clinical studies (Moya et al, 2002;Reynolds et al, 2017). Besides being a vasodilator, ethyl nitrite is also a potent nitrosating agent with possible physiological or pathophysiological consequences locally in the stomach as well as systemically after absorption.…”
Section: Nutritional Aspects Interaction Of Nitrate With Other Dietary Compoundsmentioning
confidence: 99%
“…Notably, a cross-species dimorphism in arginine metabolism was identified in a non-targeted analysis and further validated using stable isotope-labeled arginine tracing. We highlight this pathway, given the importance of nitric oxide (NO) as an RBC-transported signaling molecule that modulates vascular responsiveness to hypoxia (Doctor and Stamler, 2011); in addition, NO depletion may be a relevant component of the storage lesion that affects transfusion efficacy (Bennett-Guerrero et al, 2007;Kanias et al, 2013;Reynolds et al, 2018). Further, in the context of cardiovascular disease (CVD), RBC imbalances in arginase and NO synthase suggest that increased RBC arginase-1 activity decreases NO bioavailability, superoxide production, endothelial dysfunction, and enhances post-ischemic cardiac failure (Yang et al, 2018;Mahdi et al, 2019;Pernow et al, 2019).…”
Section: Introductionmentioning
confidence: 99%